Optimum Pressurization Mechanism for a Non-Electrical Piston-Driven Infusion Pump - Kar-Hooi Cheong; Ryouji Doihara; Noriyuki Furuichi; Masaharu Nakagawa; Ruriko Karasawa; Yoshihiro Kato; Kazunori Kageyama; Takuro Akasaka; Yuki Onuma; Takashi Kato (Applied Sciences, 2022)
Intravenous (IV) fluid therapy is a common current medical practice, and the method has remained unchanged for more than a century. The IV bag is suspended from an IV stand or pole, and the pressure created by gravity is used to administer the drug. However, this method inevitably reduces the mobility of patients, and may cause accidents such as falls during movement. To solve these problems faced in home care, nursing home, and hospital settings, this study aims to develop a non-hanging, non-electrically driven IV infusion pump with reasonable portability and operability. In this study, instead of gravity, atmospheric pressure was used as the driving force. We developed several prototypes based on different pressurization mechanisms using vacuum piston cylinders as the driving mechanism, in order to find an optimum mechanism capable of producing a stable flow rate comparable to the suspended drip system. Tests on performance in terms of discharge flow rate were conducted on three feasible prototypes, based on three different pressurization mechanisms, using a gravimetric test bench built for this purpose. The tests showed that the pressurization mechanism using an inflating sleeping-bag-shaped air bag to compress a drip bag achieved the best performance in terms of flow rate stability.